Apelles und Hermogenes : zwei theologische Lehrer des zweiten Jahrhunderts - Greschat, Katharina. (Vigiliae Christianae, Supplements, 2000)
This volume deals with the intellectual and social context of two Christian teachers living in the second half of the second century. It presents a coherent reconstruction and interpretation of their teaching, often considered to be marginal within the development of early Christian doctrine. The first part of the book seeks to understand the Marcionite Apelles as a cultured person, who shaped his understanding of Christian doctrine in the context of the philosophical background and in permanent discussion with other Christian schools. In this respect Apelles coincides with the Christian Platonist Hermogenes. His opinions are described in the second part of the book. The author points out that teachers like Apelles and Hermogenes had to answer the questions of the educated in order to defend and to define their understanding of Christian faith.